1999
DOI: 10.1046/j.1365-2648.1999.01022.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific determinants of intrinsic work motivation, burnout and turnover intentions: a study among nurses

Abstract: This study of 156 Dutch general hospital nurses tested a theoretically derived model of specific relationships between work stressors and stress reactions. The model proposes four central domains of the work situation, namely work content, working conditions, social and labour relations, and conditions of employment. In addition, the model proposes three important stress reactions, namely a diminished intrinsic work motivation, occupational burnout and an inclination to leave the job. More specifically, it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
220
0
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(250 citation statements)
references
References 35 publications
23
220
0
7
Order By: Relevance
“…For example, a recent study of Bakker and Sanz-Vergel (2013) shows how nurses' self-efficacy and optimism predict work engagement only in weeks when emotional demands were higher. This was not the case for work pressure that was perceived as a hindrance by nurses in order to fulfil their work (Janssen et al, 1999). Similar results were reported by De Jonge, Le Blanc, Peeters and Noordam (2008) in a study with nurses and others health employees, who found that high emotional demands predict creativity and work motivation when there are job resources available.…”
Section: Introductionsupporting
confidence: 75%
“…For example, a recent study of Bakker and Sanz-Vergel (2013) shows how nurses' self-efficacy and optimism predict work engagement only in weeks when emotional demands were higher. This was not the case for work pressure that was perceived as a hindrance by nurses in order to fulfil their work (Janssen et al, 1999). Similar results were reported by De Jonge, Le Blanc, Peeters and Noordam (2008) in a study with nurses and others health employees, who found that high emotional demands predict creativity and work motivation when there are job resources available.…”
Section: Introductionsupporting
confidence: 75%
“…Particularly with regard to 'people's work', which often implies intensive emotional experiences, social support from colleagues and superiors may help workers to cope effectively with these experiences. A meta-analytic study by Janssen et al [27] provides evidence for the relationship existing between demands (workload) and lack of resources (limited social support) on the one hand, and emotional distress on the other. Social support from colleagues and supervisors can be very helpful in reducing and preventing emotional distress.…”
Section: Discussionmentioning
confidence: 99%
“…[8,10,32] This is in line with health professionals' in-trinsic motivation to strive to do their best for the patients as well as to develop their medical and care competence. [33][34][35] Health professionals' intention to do their best to create value for the patients probably explains their interest in participating in teams leading implementation work. Another explanation might be that implementing VBHC was seen as a break in the NPM trend.…”
Section: Discussionmentioning
confidence: 99%